GROWTH REGULATORS AND PHYSICAL STATE OF CULTURE MEDIA IN THE MICROPROPAGATION OF ORNAMENTAL PINEAPPLE HYBRIDS - VIDIGAL DUARTE SOUZA, FERNANDA; DA SILVA, MARIANE DE JESUS; DA SILVA SOUZA, ANTÔNIO; PEREIRA DE CARVALHO COSTA, MARIA ANGÉLICA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
The aim of this work was to evaluate the effect of different combinations of two growth regulators (6-benzilaminopurin - BA and naphthalene acetic acid - NAA) in solid and liquid culture media on the micropropagation of ornamental pineapple in order to produce shoots and seedlings in large scale. Buds obtained from pineapple’s crown were used as initial explants. The explants were cultivated in MS media supplemented with 0.89 µM BAP, 0.05 µM NAA and 3% sucrose. Forty five days after culture the buds were transferred to different media. The factorial combinations were three ornamental pineapple hybrids (FRF- 1392 X FRF-32, G-44 X FRF-1387 and Carauá Roxo X Ananás Tricolor); two physical culture medium states (solid and liquid); four culture media (M01 – MS control; M02 – MS + 2.68 µM NAA; M03 – MS + 2.22 µM BAP; M04 – MS + 2.68 µM NAA + 2.22 µM BAP), consisting of 24 treatments. After 45 and 90 days of culture in growth chamber, number of shoots, height of shoots and number of roots were evaluated. Data were analyzed using analysis of variance and comparisons of means were conducted using the Tukey test at 1% probability. Significant differences were observed among the three hybrids under different treatments. The highest multiplication rates were obtained with M03 and M04 liquid culture medium and the best results were obtained with the FRF-1392 X FRF-32 hybrid.